HTLV-1 associated acute adult T-cell lymphoma/leukemia presenting as acute liver failure in Micronesian: A case report. Issue 28 (16th July 2021) - Ghaffari-Rafi, Arash; Rho, Young Soo; Hall, Andrew; Villanueva, Nicolas; Nogi, Masayuki
Abstract: Rationale: Malignant infiltration accounts for 0.5% of acute liver failure cases, with non-Hodgkin's lymphoma the predominant cause. Adult T-cell lymphoma/leukemia (ATLL) is a rarer source of acute hepatitis, with only 3 cases reported and all resulting in immediate deterioration with death. ATLL rises from human T-lymphocytic virus-1 (HTLV-1), commonly found in Japan (southern and northern islands), the Caribbean, Central and South America, intertropical Africa, Romania, and northern Iran. In Micronesia, HTLV-1 infection amongst native-born is absent or exceedingly rare. Patient Concerns: A 77-year-old Marshallese man presented to the emergency department with a 1-week history of generalized weakness, fatigue, and nausea. The physical exam revealed a cervical papulonodular exanthem and scleral icterus. Diagnosis: Laboratory studies were remarkable for aspartate-aminotransferase of 230 IU/L (reference range [RR]: 0–40), alanine-aminotransferase of 227 IU/L (RR: 0–41), alkaline phosphatase of 133 IU/L (RR: 35–129), and total bilirubin of 4.7 mg/dL (RR: 0–1.2), supporting acute liver injury. Platelet count was 11.6x10 4 /μL (RR: 15.1–42.4 × 10 4 ), hemoglobin was 13.8 g/dL (RR: 13.7–17.5), and white blood cell count was 7570/μL (RR: 3800–10, 800) with 81.8% neutrophils (RR: 34.0–72.0) and 10.4% lymphocytes (RR: 12.0–44.0). The peripheral blood smear demonstrated abnormal lymphocytes with occasional flower cell morphology. HTLV-1/2 antibody tested positive. The skin and liver biopsies confirmed atypical T-cell infiltrate. The diagnosis of ATLL was established. Interventions: The patient elected for palliative chemotherapy with cyclophosphamide, vincristine, and prednisone (CVP). He began antiviral treatment with zidovudine 250 mg bis in die (BID) indefinitely. Ursodiol and cholestyramine were added for his hyperbilirubinemia. Outcomes: Four weeks from admission, the patient returned to near baseline functional status and was discharged home. Lessons: This case highlights that ATLL can initially present as isolated acute hepatitis, and how careful examination of peripheral blood-smear may elucidate hepatitis etiology. We also present support for utilizing ursodiol with cholestyramine for treating a hyperbilirubinemia. Moreover, unlike prior reports of ATLL presenting as liver dysfunction, combined antiviral and CVP chemotherapy was effective in this case. Lastly, there are seldom demographic reports of HTLV-1 infection from the Micronesian area, and our case represents the first indexed case of HTLV-1-associated-ATLL presenting as acute liver failure in a Marshallese patient.